Computer system of increase of the efficiency of diamond polishing on the basis of treatment of indirect measuring data - Yenikieiev, O. F. (Visnyk of Vinnytsia Politechnical Institute, 2014)
Conception of construction of the application-oriented distributed computer system is suggested on the basis of treatment of the data of indirect measuring. The simulation models of channels are built and efficiency of the system is set.